Profit Sharing and Auto Workers' Earning: The United States vs Canada - Katz, Harry; Meltz, Noah (Relations industrielles / Industrial Relations, 1991)
In response to the 1981-82 recession and demands for concessions the auto workers in the United States (UAW) accepted contracts that shifted away from the three decades-old annual improvement factor and included profit sharing plans. In Canada the Canadian branch of the UAW negotiated wage increases that differed from those in the U.S. and did not include profit sharing. Over the period 1982 to 1989, in terms of direct monetary earnings alone, American auto workers received less than their Canadian counterparts. This paper examines the sources of the differences in earnings for each of General Motors, Ford and Chrysler.